SCIENTIFIC AND THEORETICAL BASIS OF INCLUSIVE EDUCATION OF STUDENTS WITH DISABILITIES (British Journal of Global Ecology and Sustainable Development, 2026)
This article discusses the scientific and theoretical foundations of inclusive education for students with disabilities, highlighting the essence of inclusive learning, its main principles, as well as pedagogical, psychological, and social aspects. The role of the teacher in the inclusive education process, the legal framework, and the factors that contribute to improving the quality of education are also analyzed. The article provides a scientific and theoretical justification of the importance of inclusion in the modern education system and the mechanisms for supporting students with disabilities.